1997
DOI: 10.1021/bi962012w
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Type A and B Phytochromes from Potato. Transient Absorption Spectroscopy

Abstract: The cDNAs encoding full-length type A and B phytochromes (phyA and phyB, respectively) from potato were expressed in inducible yeast systems (Saccharomyces cerevisiae and Pichia pastoris). In addition, a deletion mutant of phyB (delta 1-74) was expressed. The apoproteins were reconstituted into chromoproteins by incorporation of the native chromophore, phytochromobilin (P phi B), and of phycocyanobilin (PCB). The incorporation of P phi B yielded chromoproteins with difference absorptions lambda max at 660 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 37 publications
6
51
0
Order By: Relevance
“…Hence, characterization of the molecular interaction between the chromophore and the apoprotein is crucial for understanding the functional mechanism(s) of phytochromes. Several studies have addressed this interaction by using in vitro assembly of PHYA (5,28,29,47), PHYB (35,37,48), PHYC and PHYE (43), or apoprotein mutants (30)(31)(32). However, in contrast to the vertebrate photoreceptor rhodopsin (49), in the phytochrome field, little has been done to examine the relationships among chromophore structure, its assembly to apoprotein, and photochromism of the holoprotein, because of the difficulty of synthesizing the chromophore and its structural analogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, characterization of the molecular interaction between the chromophore and the apoprotein is crucial for understanding the functional mechanism(s) of phytochromes. Several studies have addressed this interaction by using in vitro assembly of PHYA (5,28,29,47), PHYB (35,37,48), PHYC and PHYE (43), or apoprotein mutants (30)(31)(32). However, in contrast to the vertebrate photoreceptor rhodopsin (49), in the phytochrome field, little has been done to examine the relationships among chromophore structure, its assembly to apoprotein, and photochromism of the holoprotein, because of the difficulty of synthesizing the chromophore and its structural analogs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PhyB has not been well characterized because of its low abundance in native tissue. Recently, several groups reported in vitro assembly of PhyB and showed that it has similar spectral properties to PhyA (35)(36)(37).…”
mentioning
confidence: 99%
“…Several groups have reported in vitro assembly of PhyB and have shown that it has similar spectral properties to PhyA. [134][135][136] To analyze the structural requirements of the chromophore for the spectral properties of PhyB, we designed and chemically synthesized more than 20 bilin chromophore derivatives (Fig. 10), including natural PÈB and PCB, and reconstituted them with recombinant Arabidopsis PhyB apoprotein (PHYB) through collaborative study with biologists.…”
Section: Assembly Of the Synthetic Bilin Chromophoresmentioning
confidence: 99%
“…Arabidopsis phyB transcripts were probed with a 3.9-kb KpnI fragment generated from pMAB316 and potato phyB transcripts with a 2.7-kb HpaI/ KpnI fragment of a plasmid encoding the full-length cDNA (Ruddat et al, 1997). Probes against the potato ribosomal protein S4 (Devi et al, 1989) served to normalize for equal loading of poly(A ϩ ) RNA.…”
Section: Rna Extraction and Northern Analysismentioning
confidence: 99%